When and how should we use imaging in individuals at risk of rheumatoid arthritis? - Harnden, Kate; Di Matteo, Andrea; Mankia, Kulveer (Frontiers in Medicine, 2022)
In recent years rheumatologists have begun to shift focus from early rheumatoid arthritis (RA) to studying individuals at risk of developing the disease. It is now possible to use blood, clinical and imaging biomarkers to identify those at risk of progression before the onset of clinical synovitis. The use of imaging, in particular ultrasound (US) and magnetic resonance imaging (MRI), has become much more widespread in individuals at-risk of RA. Numerous studies have demonstrated that imaging can help us understand RA pathogenesis as well as identifying individuals at high risk of progression. In addition, imaging techniques are becoming more sophisticated with newer imaging modalities such as high-resolution peripheral quantitative computed tomography (HR-pQRCT), nuclear imaging and whole body-MRI (WB-MRI) starting to emerge. Imaging studies in at risk individuals are heterogeneous in nature due to the different at-risk populations, imaging modalities and protocols used. This review will explore the available imaging modalities and the rationale for their use in the main populations at risk of RA.